2018
DOI: 10.1111/jocn.14311
|View full text |Cite
|
Sign up to set email alerts
|

Impact of workplace violence against nurses’ thriving at work, job satisfaction and turnover intention: A cross‐sectional study

Abstract: Workplace violence and its negative impact on nursing work should not go unnoticed by nursing managers. Nurses' subjective well-being is critical in controlling and mitigating the adverse effects of workplace violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
113
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 67 publications
9
113
0
4
Order By: Relevance
“…Furthermore, the current study identifies a negative association between nurses' exposure to violence and job satisfaction. This finding accords with previous research studies (Budin, Brewer, Chao, & Kovner, ; Munoz, Zaragoza, Ruiz Hernandez, & Jimenez‐Barbero, ; Purpora & Blegen, ; Zhao et al, ). For instance, Purpora and Belgen () identified a statistically significant negative relationship between workplace violence and job satisfaction.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the current study identifies a negative association between nurses' exposure to violence and job satisfaction. This finding accords with previous research studies (Budin, Brewer, Chao, & Kovner, ; Munoz, Zaragoza, Ruiz Hernandez, & Jimenez‐Barbero, ; Purpora & Blegen, ; Zhao et al, ). For instance, Purpora and Belgen () identified a statistically significant negative relationship between workplace violence and job satisfaction.…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis of these eleven studies reveals differences among the average scores recorded for each dimension of burnout syndrome among mental health nurses. Analysis of the results for each dimension reveals moderate-high levels of stress-related emotional exhaustion and depersonalization, usually due to organizational problems which lead to a situation of work overload (Cañadas-De la , and hence emotional overload and job dissatisfaction (Zhao et al 2018). Another negative factor is that of excessive commuting distance, which considerably limits nurses' possibilities of taking part in professional training activities (Kulig et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of violence on health organisations are considerable. International studies have shown how the physical and emotional effects on nursing staff, such as absence due to work injury or sick days (Pompei et al., ), absenteeism (O'Brien‐Pallas, Hayes, Wang, & Laporte, ), the intention to leave (Choi & Lee, ), burnout (Liu et al., ) and job satisfaction (Zhao et al., ), strongly impact on the budgets of administrators, both regarding direct and indirect costs (Speroni, Fitch, Dawson, Dugan, & Atherton, ). In Emergency Departments (ED), violence towards health professionals is so common that Emergency nurses consider these episodes as “a part of the job” (Copeland & Henry, ; Pich, Kable, & Hazelton, ) and WPV as the “dark side of the Emergency Department” (Ray, ).…”
Section: Introductionmentioning
confidence: 99%